Men in a Developing Society Geographic and Social Mobility in Monterrey, Mexico - Balán, Jorge (University of Texas Press, 2021)
The central objective of Men in a Developing Society is to show, as concretely as possible, how men experience a period of rapid economic development, particularly in the areas of migration, occupational mobility, and status attainment. It is based mainly on a sample of 1,640 men in Monterrey, Mexico, a large and rapidly growing manufacturing metropolis in northern Mexico with much in-migration, and a sample of 380 men in Cedral, San Luis Potosí, a small, economically depressed community with high rates of out-migration, much of it to Monterrey. The study of men in Monterrey is perhaps the most thorough one yet conducted of geographic and social mobility in a Latin American city. In part, this was possible because of the innovation of collecting complete life histories that record what each man was doing for any given year in the lay areas of residence, education, family formation, and work.